PENGARUH PROMOSI PENJUALAN SHOPEEFOOD DI MEDIA SOSIAL INSTAGRAM @SHOPEEFOOD_ID TERHADAP KEPUTUSAN PEMBELIAN (Survei pada Followers Instagram @shopeefood_id) - Ersha Eigidea Ratu Zahira, (2023)
Current technological advances can be utilized as best as possible in any activity, one of which is marketing communications. Promotion is one of the elements of the marketing mix used by ShopeeFood. The form of promotion carried out by ShopeeFood via Instagram @shopeefood_id is a routine beautiful date promo. Therefore this study aims to determine how much influence ShopeeFood sales promotions on Instagram social media have on purchasing decisions. The theory used by researchers is AISAS (Attention, Interest, Search, Action, Share) with a descriptive quantitative method with a positivistic paradigm and purposive sampling data collection techniques. The results obtained in this study stated that routine beautiful date promos on Instagram @shopeefood_id had a significant influence on purchasing decisions and the correlation of variable X with variable Y also had a very strong relationship as evidenced by a correlation test value of 0.825. Based on the results of the simple linear regression test, it can be concluded that variable X has a positive value and it can be interpreted that the higher the value obtained from the sales promotion, the more it will affect the purchase decision. Based on the results of the analysis of hypothesis testing, it can be concluded that t count 49.023 > t table 1.660, then Ho is rejected and Ha is accepted, which means that there is an influence of variable X routine sales promotions on beautiful dates on Instagram @shopeefood_id. on Instagram social media on purchasing decisions.